2015
DOI: 10.3109/02699206.2015.1052563
|View full text |Cite
|
Sign up to set email alerts
|

Limited acquisition and generalisation of rhotics with ultrasound visual feedback in childhood apraxia

Abstract: Ultrasound visual feedback of the tongue is one treatment option for individuals with persisting speech sound errors. This study evaluated children's performance during acquisition and generalisation of American English rhotics using ultrasound feedback. Three children aged 10–13 with persisting speech sound errors associated with childhood apraxia of speech (CAS) were treated for 14 one-hour sessions. Two of the participants increased the accuracy of their rhotic production during practice trials within treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 52 publications
2
34
0
2
Order By: Relevance
“…The challenge in CAS treatment with a motor speech focus is that the clinician's success in evoking and shaping increasingly correct, precise, and stable speech and prosody (i.e., shaping) is dependent on the integrity of processes that both precede (representational and feedforward) and follow (auditory and somatosensory feedback) the person's speech productions. The claim here, again, is that the present findings indicate that although motor speech goals are necessary in CAS treatment, some research supports the perspective that motor speech goals likely are not sufficient (Preston, Maas, Whittle, Leece, & McCabe, 2016;Rvachew & BrosseauLapré, 2012).…”
Section: Treatment Goalssupporting
confidence: 68%
“…The challenge in CAS treatment with a motor speech focus is that the clinician's success in evoking and shaping increasingly correct, precise, and stable speech and prosody (i.e., shaping) is dependent on the integrity of processes that both precede (representational and feedforward) and follow (auditory and somatosensory feedback) the person's speech productions. The claim here, again, is that the present findings indicate that although motor speech goals are necessary in CAS treatment, some research supports the perspective that motor speech goals likely are not sufficient (Preston, Maas, Whittle, Leece, & McCabe, 2016;Rvachew & BrosseauLapré, 2012).…”
Section: Treatment Goalssupporting
confidence: 68%
“…Most clinical studies to date, particularly with children as participants, have used hand-held ultrasound without recording external reference points (e.g. Bacsfalvi & Bernhardt, 2011;Bressmann et al, 2011;Klein et al, 2013;Preston et al, 2016). While results of clinical studies with head-to-transducer stabilisation have been reported (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Ultrasound imaging can be particularly useful for evaluating 26,27 and remediating 2,10,11,12,13,20 speech sound errors that involve the oral and pharyngeal constrictions associated with /r/. Sagittal views can identify if the participant is lacking an anterior constriction or tongue root retraction.…”
Section: Significance Of the Technique With Respect To Existing/altermentioning
confidence: 99%
“…Coronal views provide the ability to examine whether there is midline grooving and elevation of the lateral margins of the tongue during /r/ production. Once the elements in error have been properly identified, this information can be used to systematically train new tongue movements, ideally while viewing real-time feedback of the tongue 2,10,11,12,13,20 . Methods such as electropalatography or electromagnetic articulography do not allow sufficient visualization of all aspects of the tongue, such as the tongue root, whereas ultrasound can overcome this limitation.…”
Section: Significance Of the Technique With Respect To Existing/altermentioning
confidence: 99%
See 1 more Smart Citation